Toward Perceived Sustainable Employability: Capabilities of Secondary School Teachers in a South African Context - de Wet, Tessa; Rothmann, Sebastiaan (Frontiers in Psychology, 2022)
This study aimed to identify the capabilities of secondary school teachers – valued aspects of work that are enabled and can be realized – and investigate the effects of these capabilities on three functionings: flourishing at work, organizational citizenship behavior, and intention to leave. A convenience sample of secondary school teachers (N = 144) in the Gauteng province in South Africa participated in the study. The teachers responded to the Capability Set for Work Questionnaire, Flourishing-at-Work Scale – Short Form, Organizational Citizenship Behavior Questionnaire, and Intention to Leave Scale. The results showed that three capabilities were most likely to form part of the capability set of teachers: using knowledge and skills, building and maintaining meaningful relationships at work, and contributing to something valuable. Capabilities least likely to form part of the capability set included having a good income, involvement in important decisions, and developing knowledge and skills. The capability set was a strong predictor of emotional, psychological, and social well-being, and a moderate predictor of organizational citizenship behavior and intention to leave. A capability set for work, rather than single work capabilities, seemed to be critical for the sustainable employability of secondary school teachers.